An Overview of a Supervision of the Quality of Work in Pharmacies in Belgrade in 1888 - Arsić, Jasmina; Krajnović, Dušanka (Archives of Pharmacy, 2022)
In the ninth decade of the 19th century, significant changes took place in the regulation of work in pharmacies. Medical Department of the Ministry of Internal Affairs dealt with difficulties in establishing a pharmacy network in the newly liberated parts of Serbia, as well as one state chemist, as a regular member of all the boards of supervision in Serbia. The paper aims to present the results of a regular supervision of the quality of work of six out of seven existing pharmacies in Belgrade in 1888 (except for one newly opened which was inspected at the opening). Method of historical analysis by using the primary and the secondary data sources was applied. The supervision included the control of staff, equipment, content and quality of medicines in the pharmacies. The Board of Supervision consisted of the state chemist, Dr. Ferdinand Shams, a city physicist and a representative of the Belgrade police authority. One of the pharmacies completely fulfilled the conditions, four pharmacies fulfilled partially, while only one pharmacy did not fulfill the conditions at all, provided by the Law on Regulation of the Medical Profession and Public Health (1881). The subsequent control of work, carried out six months later, showed that irregularities were only partially corrected. The Board left the owners 45 days to correct all the identified irregularities. Supervision of the pharmacy affairs in Belgrade at the end of the 19th century pointed out the irregularities needed to be eliminated in order to continue working.